PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI KEBUDAYAAN INDONESIA (SI BUDI) BERBASIS AUGMENTED REALITY UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR - Fadhil Musyaffa, Irsyad; Isdaryanti, Barokah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Researchers developed augmented reality-based learning media for social studies subjects on cultural diversity in Indonesia. This diversity includes food, clothing, traditional houses, factors that influence cultural diversity in Indonesia, and attitudes towards cultural diversity. Because the material is so extensive, students find it difficult to understand the lesson. In addition, because the teacher only uses the textbook and the lecture or one-way method, the learners' learning outcomes become worse. Analysis, design, development, implementation and evaluation are included in the type of development research (R&D) in this study with the ADDIE model. With media that has been validated by material experts with a value of 93.33% and media experts 95.65%, then from the results of students' responses of 90.60% and the results of the evaluation of class IV teachers of 96%, therefore showing that the learning media developed is very feasible to be applied in the learning process. In addition, the results of the T test and N-gain with sig. (2-tailed) of 0.0008 in the T-test and 73.46% in the N-gain test indicate that the learning tools made are effective and can help students improve their learning outcomes about cultural diversity.